Secular Messiahs and the Return of Paul’s 'Real' - Principe, C. author. aut Link
VII, 245 p.
Keywords: This project engages with scholarship on Paul by philosophers, psychoanalysts, and historians to reveal the assumptions and prejudices that determine the messiah in secularism and its association with the exception.